Kontribusi Natural Soundscape, Memorable Tourism Experience dan Natural Landscape Dalam Meningkatkan Destination Loyality Wisatawan Tahura Djuanda Bandung - Muhamad Zidane Zulfikar; Yadi Ernawadi (Universitas Respati Indonesia, 2024)
The aim of this research is to examine the influence of natural soundscape, memorable tourism experience, and natural landscape, on destination loyalty which is mediated by the emotions of Tahura Djuanda Bandung tourists. A total of 125 tourists who had experience visiting Tahura Djuanda Bandung participated in this research as respondents. The cross-sectional or one shot method is used to obtain data. The instrument has been declared a validity and reliability test which includes outer model measurements, namely convergent validity, discriminant validity and composite reliability. The data analysis technique used is structural equation modeling (SEM) using the SmartPLS version 3.0 tool. Of the ten proposed research hypotheses, eight are supported by empirical data. Natural soundscape, memorable tourism experience, and natural landscape were found to have a positive effect on emotions. Meanwhile, emotions mediate the influence of natural soundscape, memorable tourism experience, and natural landscape on destination loyalty. The results of this research provide benefits for further research and tourist destination managers in designing marketing strategies that are relevant to the concept being measured.